Digital Governance Through Self-Regulation: A user-developer perspective of AI chatbots - Navaratna, Anand R; Saxena, Deepak (Journal of Telecommunications and the Digital Economy, 2025)
User-centric development of digital applications must integrate user feedback, developer channels, and regulatory compliance, yet lacks a standardised framework. The rapid rise of AI exacerbates auditing and governance challenges, with self-regulation prevailing but requiring scrutiny of user and developer concerns. This paper analyses the top 10 AI chatbot apps on Google Play Store via a three-prong approach. First, sentiment analysis of 117,353 user reviews using two algorithms reveals sentiments on policy and governance. Second, evaluation of 15 preset developer compliance parameters shows self-declared adherence. Third, comparative results indicate only 69% compliance, despite these apps' high popularity and downloads. Users prioritise experience quality, while developers emphasise service quality. The study exposes self-regulation gaps in AI chatbots, advocating for a standard compliance score on app stores and enhanced citizen digital awareness to bridge divides.